Polynomials Theory and Applications - Ryoo, Cheon-Seoung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Polynomial and its applications are well known for their proven properties and excellent applicability in interdisciplinary fields of science. Until now, research on polynomial and its applications has been done in mathematics, applied mathematics, and sciences. This book is based on recent results in all areas related to polynomial and its applications. This book provides an overview of the current research in the field of polynomials and its applications. The following papers have been published in this volume: 'A Parametric Kind of the Degenerate Fubini Numbers and Polynomials'; 'On 2-Variables Konhauser Matrix Polynomials and Their Fractional Integrals'; 'Fractional Supersymmetric Hermite Polynomials'; 'Rational Approximation for Solving an Implicitly Given Colebrook Flow Friction Equation'; 'Iterating the Sum of Möbius Divisor Function and Euler Totient Function'; 'Differential Equations Arising from the Generating Function of the (r, β)-Bell Polynomials and Distribution of Zeros of Equations'; 'Truncated Fubini Polynomials'; 'On Positive Quadratic Hyponormality of a Unilateral Weighted Shift with Recursively Generated by Five Weights'; 'Ground State Solutions for Fractional Choquard Equations with Potential Vanishing at Infinity'; 'Some Identities on Degenerate Bernstein and Degenerate Euler Polynomials'; 'Some Identities Involving Hermite Kampé de Fériet Polynomials Arising from Differential Equations and Location of Their Zeros.'